Pengukuran Tingkat Kepuasan Produk Hand Craft di Home Industri Menggunakan Metode Servsqual dan IPA - Arista, Anggia; Nelvi, Afni (Fakultas Teknik UMRI, 2024)
Recently, businesses in the handicraft sector have been very popular with the people of Batam City. The hand craft business produces handicraft items such as plaques, name plates, acrylic house numbers, acrylic motorbike plates, acrylic boxes and others. Rusya's hand craft business already has regular customers, consumers who come from Batam City and outside Batam City. From the research results for the tangible dimension of the quality satisfaction category, the value is positive, for the reliability dimension there is 1 attribute that has a negative value, namely statement number 5 with a value of -0.16. For the responsiveness dimension, there is 1 attribute that is not satisfied with a value of -0.1, namely statement number 9, namely speed and toughness in handling consumer complaints. For the empathy dimension, namely number 15, namely the employee attribute section that cares about consumer desires when ordering products, it has a value of -0.1. Solutions that need to be improved by providing services in accordance with what has been agreed upon, providing targets for employees, providing professional workers in accordance with their fields